2014
DOI: 10.1016/j.jad.2014.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and the course of bipolar disorders among adults: Epidemiologic evidence of dose-response effects

Abstract: BACKGROUND Childhood maltreatment (CM) is highly prevalent among individuals with bipolar disorders (BP); however few studies have examined its potential role in the course and outcome of individuals with BP. We aim to examine the dose response relationship between the number of types of CM and the course of individuals with BP. METHODS As part of the National Epidemiologic Survey on Alcohol and Related Conditions, 1600 adults who met lifetime DSM-IV criteria for BP-I (n=1172) and BP-II (n=428) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
7
39
1
2
Order By: Relevance
“…Research on personality pathology has revealed that both Cluster B and C traits are common than Cluster A (George et al, 2003). Asian studies concur with the global literature that childhood maltreatment and emotional neglect in childhood are reported to have strong associations with BD in adults (Romero et al, 2009;Sala et al, 2014;Watson et al, 2014). The findings reveal that psychiatric comorbidities in BD can begin to occur at the early stages of the life and tend to worsen the illness course through various mechanisms.…”
Section: Influence Of Other Psychiatric Comorbiditiessupporting
confidence: 73%
“…Research on personality pathology has revealed that both Cluster B and C traits are common than Cluster A (George et al, 2003). Asian studies concur with the global literature that childhood maltreatment and emotional neglect in childhood are reported to have strong associations with BD in adults (Romero et al, 2009;Sala et al, 2014;Watson et al, 2014). The findings reveal that psychiatric comorbidities in BD can begin to occur at the early stages of the life and tend to worsen the illness course through various mechanisms.…”
Section: Influence Of Other Psychiatric Comorbiditiessupporting
confidence: 73%
“…For example, childhood adversity is an important indicator of a more persistent and treatment-refractory course of illness and affects response to both pharmacological and psychosocial treatment for youth and adults with mental health conditions. [91][92][93][94][95] Among people with mental health conditions, childhood adversity, compared with no childhood adversity, results in greater cumulative exposure to mental health symptoms, associated stress, and biological perturbations. [96][97][98] Beyond the direct effects of mental health problems on cardiometabolic outcomes, there are also indirect effects that further exacerbate cardiometabolic risk factors.…”
Section: Mental Health Factorsmentioning
confidence: 99%
“…133 Childhood abuse and neglect have been associated with worsening of the clinical course of BD 134 in a possible dose-response relationship. 135 Childhood abuse has further been associated with alterations in peripheral BDNF levels, 121,136 but with inconsistent findings of opposite direction of such association, leaving uncertainty as to the relationship between peripheral BDNF levels and childhood abuse. A lack of Information on childhood abuse in the included studies in the present meta-analysis did not allow for evaluation of the potential relationship between this and peripheral BDNF levels.…”
Section: Limitationsmentioning
confidence: 99%